Renewable energy in Portugal: legislation, incentives and suggestions - Moreira, M. Fernanda T. (2003)
This paper presents the evolution of renewable energy generation in Portugal in the last decade, and explains the legislation and incentives in existence. The paper also presents suggestions that could incentive small and medium consumers to install renewable energy power plants (namely of wind power and photovoltaic types) in their facilities. These power plants would have to accomplish present legislation regarding “reactive energy” production during peak power consumption period, and besides, would have to assure power quality levels. On the other hand, reversible energy meters should be used, so that it would be registered the consumption of energy from the energy company, or the delivery of energy to the energy company. The equipments which could implement these characteristics are briefly described.